2012
DOI: 10.1159/000345229
|View full text |Cite
|
Sign up to set email alerts
|

Increased Somatic Morbidity in the First Year after Leaving Opioid Maintenance Treatment: Results from a Norwegian Cohort Study

Abstract: Background/Aims: Some patients on opioid maintenance treatment (OMT) leave treatment temporarily or permanently. This study investigated whether patients interrupting their OMT differed from non-interrupters in sociodemographic and drug-use characteristics and examined acute/sub-acute somatic morbidity among the interrupters, prior to, during, and after OMT. Methods: Cohort design. Observation Period: 5 years prior to, up to first 5 years during, and up to 5 years after interruption of OMT. Participants: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
9
0
2
Order By: Relevance
“…Research has shown that mortality in this group of aging patients in OMT is more associated with comorbid somatic conditions, rather than ongoing illicit drug use [3,8,9]. A Norwegian comparison of 149 patients continuously in OMT with 51 "interrupters" showed a reduction in drug-related somatic problems for the continuous patients, but no difference in the amount of non-drug-related somatic problems between the two groups [10]. On one hand, this is a testament to OMT reducing illicit drug use over time.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that mortality in this group of aging patients in OMT is more associated with comorbid somatic conditions, rather than ongoing illicit drug use [3,8,9]. A Norwegian comparison of 149 patients continuously in OMT with 51 "interrupters" showed a reduction in drug-related somatic problems for the continuous patients, but no difference in the amount of non-drug-related somatic problems between the two groups [10]. On one hand, this is a testament to OMT reducing illicit drug use over time.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term treatment is indicative of reduced drug use, increased social functioning, and an increase in mental well-being (Fingleton, Matheson, & Holland, 2015 ; Jones, 2007 ). Interrupted treatment, however, is indicative of increased drug use and somatic issues (Skeie et al, 2013 ). As it achieves several goals, OMT is thus viewed as a successful method for treating opioid dependence.…”
mentioning
confidence: 99%
“…It is possible that the group of patients with heroin poisoning has changed as the opioid maintenance therapy programs have expanded. They may have become a more troubled group of patients, not managing to enter or remain in opioid maintenance programs, hence with a higher risk of repetition [ 34 ].…”
Section: Limitationsmentioning
confidence: 99%